Penguatan Kesadaran Anti-Bullying melalui Edukasi Interaktif pada Siswa Sekolah Dasar - Arum, Dewi Sekar; Putri, Pramesti Fadhila Pamuji; Azazi, Firly Maulana; Riyadi, Ridho; Pujiono, Imam Prayogo; Prayogi, Arditya; Nasrullah, Riki (Kolaborasi Masyarakat, 2025)
Bullying is an aggressive act carried out intentionally and repeatedly, whether physical, verbal, or social, to hurt or demean others. This phenomenon remains prevalent in elementary school environments and has negative impacts on students’ emotional and social development. This community service activity aimed to increase students’ understanding and awareness of bullying, foster empathy, and build a culture of mutual respect within the school environment. The method used was interactive counseling consisting of five stages: problem identification, planning, preparation, implementation, and evaluation. The activity involved 22 fifth-grade students of SDN 02 Banjarejo Pekalongan, using a questionnaire instrument containing 10 questions in the form of a pre-test and a post-test to measure students’ comprehension levels. The results were analyzed descriptively and quantitatively based on the percentage change between pre-test and post-test scores. The findings showed that before the socialization, 70% (15 students) did not yet understand the concept of bullying, whereas after the activity, 90% (20 students) were able to recognize its forms and impacts as well as understand preventive measures. In addition to increasing knowledge, the program also created a safe dialogue space for students to share experiences and learn assertive behavior. Therefore, this interactive educational activity proved effective in improving understanding, empathy, and mutual respect among students, serving as an initial step toward creating an inclusive and bullying-free elementary school environment.